1996
DOI: 10.1111/j.1365-3180.1996.tb01675.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nitrogen on competition between cereals and their natural weed populations

Abstract: seed production and, hence, the seed pool and future weed population, suggesting that fertilize r usage can be exploited in an integrated programme of ciopiwecd management. A trend towards lower N fertilizer application owing lo concerns about the environment willlavour most of the weed spedes investigated in these experiments and change the composition of weed populations.The effects of nitrogen fertilizer on the growth and density of natural weed populations io spring barley (Hordeum vuigare L.) and winter w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 9 publications
9
74
4
Order By: Relevance
“…Several studies report increased weed growth in high nitrogen environments [43,44]. The opposite trend was observed in our study where, as Figure 6 clearly shows, an inverse relationship exists between available nitrogen and the invasion index.…”
Section: Species Distribution and Diversitycontrasting
confidence: 66%
“…Several studies report increased weed growth in high nitrogen environments [43,44]. The opposite trend was observed in our study where, as Figure 6 clearly shows, an inverse relationship exists between available nitrogen and the invasion index.…”
Section: Species Distribution and Diversitycontrasting
confidence: 66%
“…These results are in agreement with Valenti & Wicks (1992), who found that applying N to winter wheat decreased annual grass weed populations and weed yields, as well as with those obtained by Jørnsgård et al (1996). These authors found that above dry matter of Chenopodium album, Lamiun amplexicaule, Stellaria media and Veronica spp.…”
Section: Fertilizationsupporting
confidence: 92%
“…Conversely, in other studies, applications of N favored Setaria viridis (Peterson & Nalewaja, 1992) and Avena fatua (Carlson & Hill, 1986) over wheat. Jørnsgård et al (1996) found differences in the biomass of individual weed species in both wheat and barley crops with N fertilizer applications.…”
Section: Introductionmentioning
confidence: 96%
“…Fertilization affects not only the growth of crop but also on weed population [14] [15] [16]. Previous studies have been demonstrated that fertilization can significantly affect weed community composition, density and diversity [17] [18] [19].…”
Section: N N Than Et Almentioning
confidence: 99%